An electromagnetic-structural coupling analysis of the HCCB blanket for the CFETR. (March 2019) - Wang, Ming; Lei, Mingzhun; Xu, Shuling; Lu, Mingxuan; Song, Yuntao; Lu, Kun; Pei, Kun; Xu, Kun
Abstract : The China Fusion Engineering Test Reactor (CFETR) is a superconducting magnet tokamak, and one mission is to demonstrate a full cycle of self-sustaining tritium. In this study, in order to validate the electromagnetic (EM) load distribution on the helium-cooled ceramic breeder (HCCB) blanket, a three-dimensional model of the CFETR sector was developed in the finite element software ANSYS. The system was analyzed considering a plasma major disruption scenario with an exponent current quench of 36 ms. The EM forces and the moment distribution on the blanket module as well as on the segment were calculated. Then, the EM loads were used as the input for the structural analysis of the HCCB blanket. Moreover, the results were compared to those of linear analyses to underline the effect of the non-linearity of the ferromagnetic materials on the EM load distribution of the HCCB blanket. These results indicated that the maximum equivalent stress and displacement satisfied the requirements of structural safety design. With respect to the design and optimization of CFETR, this investigation will provide technical reference and data support for the future design and optimization of the HCCB blanket. Highlights: A FE model of the CFETR sector was developed in the ANSYS to validate the HCCB blanket EM load. The mechanical design of the HCCB blanket was analyzed considering a plasma major disruption. The effect of the ferromagnetic materials on the EM load distribution of the HCCB blanket was studied.